(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The sexed semen is the result of recent technology. It is simple and relatively reliable as long as high quality semen is used. The basic concept of using sexed semen is to produce offspring of a particular gender. It is helpful in increasing the genetic gain through both sexes either female or male. The main objective of gender selection using sexed semen from genetically elite bulls is most important to meet the constant increasing demand of milk to feed the huge human population. The second most important use of sexed semen is in dairy animals to dispose of the large number of unproductive males. In India this technology is gradually implemented by many states like Kerala, Punjab, Haryana, West Bengal and several others. Despite its valuable contribution in increasing milk production it has certain limitations like high cost and lower fertility rates in Indian conditions. Poor animal management like nutrition, disease control, oestrus detection, semen handling, insemination techniques and indiscriminate breeding are some other barriers for obtaining higher efficiency. In the past sexed semen had lower success rates than conventional semen because of sperm damage during the sorting process and fewer sperm per dose. Dairy farmers prefer sexed semen for the sustainability of milk production optimising the number of herds and weight gain for early sexual maturity. Manipulating the sex of the animals has become of great interest to the dairy industry, due to several sex related traits, like milking, herd replacement and growth rates. Sexed semen is being used in India but its cost is high. By using more than 90 % of calves born are females, in standard conditional it is good to use.